Ellis–van Creveld Syndrome in Iran, a Case Report and Review of Disease Cases in Iran, Middle East - Baghianimoghadam, Behnam; Arabzadeh, Aidin; Fallah, Yousef (Acta medica Lituanica, 2021)
Introduction: Chondroectodermal dysplasia (Ellis–van Creveld syndrome (EVC)) (OMIM: #225500) is a rare skeletal dysplasia with unknown exact prevalence. EVC patients may have abnormal skeletal and extra skeletal symptoms. We report a case of EVC patient and review previous cases reported in Iran.Materials and methods: The patient was a 30 years old woman referred to our hand clinic for an extra finger in both hands. She was born to a consanguineous marriage. The patient had a history of bilateral valgus deformity of the knees, for which she underwent proximal tibial and distal femoral osteotomy. Upon examination, the patient had bilateral polydactyly and brachymetacarpia with hypotrophic fingernails. She was about 120 cm tall and had acromesomelic type dwarfism. Oral examination revealed serrated incisal margins, dental transposition, a diastema, conical teeth and, enamel hypoplasia. In the radiographic examination of upper extremity, postaxial polydactyly and polymetacarpia, enlarged distal radius, and fusion of capitate and hamate were seen. We searched online databases (Pubmed, Scopus, Google Scholar) and found 14 Iranian papers with 21 reported patients (there was no time limit). We reviewed available clinical and genetic data and the geographic origins of patients.Results: 14 articles reporting 22 EVC patients (including our patient) from Iran have been published in Persian and English (7 in Persian and 7 in English). All patients presented with characteristic EVC symptoms but were diagnosed at a relatively late age, 18 patients were born to consanguineous marriages.Conclusions: It seems that based on these studies, it is possible to identify some families with this genetic mutation. We can warn such families of the dangers of consanguineous marriage through genetic counseling before marriage. In addition, by identifying families with such problems, we can detect such anomalies in the baby earlier with more careful prenatal care.
Keywords: Ellis-van Creveld; Iran